Inter-relationships between composition, physicochemical properties and functionality of lecithin ingredients. (May 2021) - Bot, Francesca; Cossuta, Daniel; O'Mahony, James A.
Abstract: Background: Lecithin is widely used as an ingredient in the food industry due to its diverse functionality, mainly attributed to phospholipids (PL), the principal constituents. However, a systematic understanding of the functional properties of lecithin ingredients is missing in the literature. Scope and approach: This review outlines recent developments in lecithin from botanical origin and reviews the complex inter-relationships between physicochemical properties of PL in lecithin and selected techno-functional properties in micelles, liposomes and oil-in-water emulsions. Key findings and conclusions: Attributed to their polar phosphatide group and non-polar fatty acids, PL have specific molecular geometries, dissociation constants and charge, which strongly influence their functional properties in micelles, liposomes and oil-in-water emulsions. The PL profile and extrinsic factors (e.g., water, oil, hexane) influence the formation of micelles during separation of lecithin from oil using membrane filtration. In liposomes, PL profile and the presence of surface modifiers (i.e., sterols) affect the particle size and encapsulation efficiency. In emulsion systems, PL and their interaction with minerals and other functional ingredients (e.g., proteins), influence the particle size and physical stability of the oil droplets. This work provides an integrated review of the links between the composition and physicochemical properties of PL, and in turn, scientifically underpins the links between physicochemical and functional properties of lecithin. Highlights: The techno-functional properties of lecithin from botanical sources are reviewed. Micelle formation improves the degumming efficiency and oxidative stability of oil. Liposomes enriched in phosphatidylcholine (PC) have high bioactive compound loading capacity. Emulsions enriched in PC and lysophospholipids have smaller particle size and good physical stability.